The Discourse of Propaganda in Traveloka’s YouTube Advertising Videos - Saiful Akmal; Jarjani Jarjani; Ita Farida (Indonesian Journal of EFL and Linguistics, 2020)
This present study was conducted to analyze the propaganda techniques used by Traveloka in their YouTube social media advertising strategy. The material of analysis were videos taken from 2015 to 2019. Anaylsis of propaganda techniques proposed by Filene in 1937 and followed by Abd. Kadir, Hasan & Sauffiyan, 2014 were used to identify how Traveloka persuade its customers.  Finding shows that Traveloka used six techniques of propaganda in its advertising videos to; glittering generality, plain folks, card staking, visual symbol of power, music of propaganda and arousal of emotion to promote its products. The use of propaganda technique is very likely becoming one of the main reasons behind their customers and target audiences use of their services.